2020
DOI: 10.3390/e22040462
|View full text |Cite
|
Sign up to set email alerts
|

Day and Night Changes of Cardiovascular Complexity: A Multi-Fractal Multi-Scale Analysis

Abstract: Recently, a multifractal-multiscale approach to detrended fluctuation analysis (DFA) was proposed to evaluate the cardiovascular fractal dynamics providing a surface of self-similarity coefficients α(q,τ), function of the scale τ, and moment order q. We hypothesize that this versatile DFA approach may reflect the cardiocirculatory adaptations in complexity and nonlinearity occurring during the day/night cycle. Our aim is, therefore, to quantify how α(q, τ) surfaces of cardiovascular series differ between dayti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…, which is quite similar to the alpha short-term coefficient reported by [ 47 ], to , but takes into account the excessive deviations introduced by the method in alpha values at the shortest scales, typically [ 26 , 28 ].…”
Section: Methodssupporting
confidence: 68%
“…, which is quite similar to the alpha short-term coefficient reported by [ 47 ], to , but takes into account the excessive deviations introduced by the method in alpha values at the shortest scales, typically [ 26 , 28 ].…”
Section: Methodssupporting
confidence: 68%
“…As an application on real biomedical signals, we considered the same 24 h blood pressure recordings in healthy participants of a previous study that demonstrated differences between daytime and night-time in the α(q, n) coefficients of the heart rate [12]. Therefore, the α CF (n) index proposed in the present work could clarify whether the previously observed differences regard not only the value of the coefficients but also the degree of multifractality.…”
Section: (D) Heart Rate Seriesmentioning
confidence: 93%
“…Each pulse wave was identified on the blood pressure signal sampled at 170 Hz, artefacts and premature beats were removed, and the series of inter-beat intervals (IBI) was derived beat by beat. Details on the participants and signal acquisition and preelaboration are provided in [12]. In each IBI series, we selected two segments of N ≥ 14 000 beats, in the afternoon ('Day' period) and after 23.00 ('Night' period), and calculated F q (n) as in equation ( 2.3) for 6 < n < N/4 beats, −5 ≤ q ≤ + 5, with detrending polynomials of order 1 and 2.…”
Section: (D) Heart Rate Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results support the hypothesis of cardiovascular self-organized criticality and provide evidence of a different distribution of bradycardic sequences in the participants who experienced syncope symptoms during the test. Furthermore, cardiovascular multifractality is the topic of the paper by Castiglioni et al [ 12 ] that quantifies the multifractal–multiscale structure of the heart-rate and blood-pressure series, revealing night/day modulations of nonlinear fractal components at specific temporal scales. The work suggests that the multifractal–multiscale approach improves the clinical value of the 24 h analysis of blood pressure and heart rate variability.…”
mentioning
confidence: 99%